Plataforma de Testes de Algoritmos de Controle para Sistemas em Tempo Real - Costa Filho, Pedro Turibe (2006)
The conception, design and synthesis of a platform to evaluate the performance of the in real time control algorithms is the main focuses of this Master Thesis. For conception purpose, the platform is classi¯ed in structural and functional parts, the structural one is composed of the hardware that are sensors, actuators, controllers and related devices. The functional part is formed by algorithms to manager the platform resources and real time control strategies. The platform is dedicated to the speed control of a direct current motor and the temperature control of an electric furnace. These plants are used to develop methods for real time control, parameter estimation and controller tuning. The parameter estima- tion of the motor and furnace is performed in the platform, the obtained models are used to design the PID controller optimal gains.